The impact of a male CEO'S facial masculinity on leverage - Nur Fadjrih Asyik; Muchlis Muchlis; Ikhsan Budi Riharjo; Rusdiyanto Rusdiyanto (Cogent Business & Management, 2022)
The purpose of this study was to obtain empirical evidence of the effect of male CEO's facial masculinity on leverage, to identify the effect of male CEO's facial masculinity on leverage. This study uses a quantitative approach with a population and research sample using companies on the Indonesia Stock Exchange in 2016-2021. The study collected images of faces identified as male CEOs from data from the Indonesia Stock Exchange website and company websites and using Google searches. The panel data analysis method in this study uses Regression Ordinary Least Square (OLS) with Stata Software which connects theories, concepts and data that can be carried out on research variables. The findings suggest that the higher the value of male CEOs' facial masculinity, the greater the effect on reducing corporate leverage, and vice versa, the lower the value of male CEOs' facial masculinity, the greater the impact on increasing corporate leverage value. The practical implications of this study can help the Indonesian Association of Accountants in developing accounting in Indonesia. Meanwhile, the theoretical implications of this study can explain agency theory and behavioral consistency theory. As for the policy implications of this study, it could provide empirical evidence that male CEOs' masculinity undermines corporate leverage. To date, researchers in Indonesia have not identified significant research on the topic of masculinity of male CEOs in relation with leverage, or the characteristic role of male CEOs in influencing leverage policy. This study contrasts previous findings of a study that was conducted in the United States from 1993 to 2008. Meanwhile, the sampling period for this study was from 2016 to 2021 and was conducted in Indonesia.
Keywords: G32; G34; G02; M1; Z1; 650; leverage; CEO male; masculinity; Stata